DISCOVERY LEARNING MODELS FOR TRAINING SCIENCE LITERACY OF STUDENTS IN COLOID MATERIALS - Norbaiti, Norbaiti; Erika, Farah; Sukemi, Sukemi (PROSIDING SEMINAR KIMIA, 2023)
Scientific literacy ability is one of the abilities that must be mastered by students in the 21st century, to be able to solve problems in everyday life using the chemical concepts they are learning. Therefore, we need a learning that is able to relate learning material to the processes of everyday life, namely the effectiveness of the Discovery Learning model. The purpose of this research is to improve students' scientific literacy skills in colloid material. This Discovery Learning model focuses on student activities in learning with the teacher as the facilitator. The research method used was the pre-experimental method with a one-group pre-test-post-test design. The population in this study were all 52 students in class XI IPA at SMA Negeri 3 Muara Muntai in the 2022/2023 academic year, which were divided into 2 classes selected using a saturated sampling technique. The instruments used to measure students' scientific literacy skills are essay test techniques and non-test techniques in the form of student observation sheets and student response questionnaires. The results showed that the increase in students' scientific literacy skills was in the medium category with an effect size classified as a very strong category, as well as a positive response from students. Based on the research that has been done, it can be concluded that the effectiveness of the Discovery Learning learning model can increase students' scientific literacy in colloidal material. Keywords: Scientific Literacy, Discovery Learning Model, Colloid